2020
DOI: 10.1080/17453674.2020.1802682
|View full text |Cite
|
Sign up to set email alerts
|

Migration of the uncemented Echo Bi-Metric and Bi-Metric THA stems: a randomized controlled RSA study involving 62 patients with 24-month follow-up

Abstract: Background and purpose — Despite the good results after total hip arthroplasty (THA), new implants are continuously being developed to improve durability. The Echo Bi-Metric (EBM) THA stem is the successor to the Bi-Metric (BM) THA stem. The EBM stem includes many of the features of the BM stem, but minor changes in the design might improve the clinical performance. We compared the migration behavior with radiostereometric analysis (RSA) of the EBM stem and the BM stem at 24 months and evaluated the clinical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…Few studies have investigated migration of the Bi-Metric stem, although it is a widely used cementless stem in Nordic countries. 9 , 23 We found that stem group migrations primarily occurred within the first six weeks, which is in accordance with the current literature. 9 , 23 It has been suggested that early stem subsidence (< two years) increases the risk of later aseptic stem loosening in various cementless femoral stem types.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Few studies have investigated migration of the Bi-Metric stem, although it is a widely used cementless stem in Nordic countries. 9 , 23 We found that stem group migrations primarily occurred within the first six weeks, which is in accordance with the current literature. 9 , 23 It has been suggested that early stem subsidence (< two years) increases the risk of later aseptic stem loosening in various cementless femoral stem types.…”
Section: Discussionsupporting
confidence: 92%
“… 9 , 23 We found that stem group migrations primarily occurred within the first six weeks, which is in accordance with the current literature. 9 , 23 It has been suggested that early stem subsidence (< two years) increases the risk of later aseptic stem loosening in various cementless femoral stem types. 5 In the present study, both stem groups showed a stable migration pattern both in the short term and long term, with no group differences.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that migration thresholds are specific to the design of the stem, and that it is the pattern of migration of cementless stems that predicts their failure in THA. 24 Thus, if early stabilization is obtained and stems remain stable at follow-up, the risk of loosening and revision decreases.…”
Section: Discussionmentioning
confidence: 99%
“…All patients included took part in a prospective randomized clinical RSA trial with 2-year follow-up, where the patients were randomly allocated to receive 1 of 2 uncemented femoral stems (Dyreborg et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our study is partly based on secondary endpoint data from a randomized controlled trial (RCT) (Dyreborg et al. 2020 ). The main aim of the present study was to evaluate whether preoperative BMD of 3 regions in the femoral bone is related to femoral stem subsidence in uncemented THA.…”
mentioning
confidence: 99%